Defective Rate Reduction from Foreign Matter Contamination in Female Connector Plug Manufacturing Process - Ngamsamrong, Atthaphon; Osothsilp, Napassavong (Srinakharinwirot University Engineering Journal, 2023)
The objective of this research is to reduce defective rate from foreign matter contamination defect of Female Connector by applying the approach of Six Sigma (DMAIC) , which consists of 5 phases; starting from the Define phase, in which the injection molding process of 6P model was studied. Secondly, in the Measure phase, the required sample size was calculated, and the Attribute Agreement Analysis was performed. Then, in the Analyze Phase, it was found that there were 5 significant factors related to the defective rate. In the Improvement phase, two non-adjustable factors have been improved by creating a new particle cover to be more closely and set the cleaning frequency to 1 time per shift. The central composite design was performed for the remaining 3 adjustable factors and determined the optimum levels. The optimum values are the mold opening speed of 30 millimeters per second, delay time of 1 second and runner pushing pressure of 15 bar. Finally, work instructions and control plan have been revised in the Control phase. Which after tracking process improvement results, it was found that the defective rate from contamination defects of 6P female connector plug was reduced from 2.36% to 0.78%, which was reduced by 1.58%. In additional, the defective cost was reduced from 5,499,036 baht to 1,826,099 baht, which equivalent to a cost a saving of 3,672,937 baht per year.